2013
DOI: 10.1186/1471-2458-13-990
|View full text |Cite
|
Sign up to set email alerts
|

Impact of training of teachers on their ability, skills, and confidence to teach HIV/AIDS in classroom: a qualitative assessment

Abstract: BackgroundConsidering the significant impact of school-based HIV/AIDS education, in 2007, a curriculum on HIV/AIDS was incorporated in the national curriculum for high school students of Bangladesh through the Government’s HIV-prevention program. Based on the curriculum, an intervention was designed to train teachers responsible for teaching HIV/AIDS in classes.MethodsIn-depth interviews were conducted with teachers to understand their ability, skills, and confidence in conducting HIV/AIDS classes. Focus-group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 21 publications
2
10
0
Order By: Relevance
“…These findings of the current study are consistent with those of studies conducted by Sarma, Islam, and Gazi (2013) and Sarma, Islam, Khan, Chowdhury, & Gazi (2017).…”
Section: Impact Of Hiv/aids Education Through Fct On Secondary and Hisupporting
confidence: 93%
“…These findings of the current study are consistent with those of studies conducted by Sarma, Islam, and Gazi (2013) and Sarma, Islam, Khan, Chowdhury, & Gazi (2017).…”
Section: Impact Of Hiv/aids Education Through Fct On Secondary and Hisupporting
confidence: 93%
“…In similar studies, while training may have improved confidence to teach, the subsequent implementation of education may not occur due to the lack of motivation, time and resources (Bellissimo-Rodrigues et al, 2015). Future evaluation of impact could be measured through a case-control study, as demonstrated by Sarma and colleagues with an HIV-related training intervention for school educators (Sarma et al, 2013). A study in progress in South Gloucestershire may provide insight into the impact of the training of educators on the handwashing behaviour of primary students following education; however, the sample size of educators in this study is small (South Gloucestershire Council, 2013).…”
Section: Implications and Future Workmentioning
confidence: 99%
“…The teachers' feedbacks were similar to another study in Bangladesh. The teachers in that study perceived benefit of the prepared lesson and reduced their misconception after joining the training session (Sarma, Islam, & Gazi, 2013). A sensitive sensitive and quite a technical topic such as SRH is best to be taught for at least six days, especially for those without any experience learning it.…”
Section: Discussionmentioning
confidence: 88%